2023
DOI: 10.1021/acsami.3c12381
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Protein Impact on Early-Stage In Vitro Biodegradation of Magnesium Alloy (WE43)

Amin Imani,
Ehsan Rahimi,
Maria Lekka
et al.

Abstract: Mg and its alloys are promising biodegradable materials for orthopedic implants and cardiovascular stents. The first interactions of protein molecules with Mg alloy surfaces have a substantial impact on their biocompatibility and biodegradation. We investigate the early-stage electrochemical, chemical, morphological, and electrical surface potential changes of alloy WE43 in either 154 mM NaCl or Hanks' simulated physiological solutions in the absence or presence of bovine serum albumin (BSA) protein. WE43 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
(224 reference statements)
0
0
0
Order By: Relevance
“…Tiyyagura et al studied the corrosion behavior of plasma-modified magnesium alloys AZ91 in simulated body fluid (SBF) solution, which increased the corrosion resistance of alloys in body fluids. Imani et al investigated the impact of albumin in the initial vitro biodegradation of WE43 and found that bovine serum albumin acted as a corrosion inhibitor in NaCl solution but accelerated the degradation rate in Hanks solution. Yun et al studied the degradation behavior of the AZ91 magnesium alloy in 0.9% NaCl solution, Hank’s solution, PBS, c-SBF, and DMEM solution, indicating that the concentration of buffers and bicarbonates in the simulated body fluids had a significant effect on the degradation behavior of biomedical magnesium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Tiyyagura et al studied the corrosion behavior of plasma-modified magnesium alloys AZ91 in simulated body fluid (SBF) solution, which increased the corrosion resistance of alloys in body fluids. Imani et al investigated the impact of albumin in the initial vitro biodegradation of WE43 and found that bovine serum albumin acted as a corrosion inhibitor in NaCl solution but accelerated the degradation rate in Hanks solution. Yun et al studied the degradation behavior of the AZ91 magnesium alloy in 0.9% NaCl solution, Hank’s solution, PBS, c-SBF, and DMEM solution, indicating that the concentration of buffers and bicarbonates in the simulated body fluids had a significant effect on the degradation behavior of biomedical magnesium alloy.…”
Section: Introductionmentioning
confidence: 99%